Path planning of hyper‐redundant manipulators for narrow spaces. Issue 3 (16th September 2022) - Su, Haoxiang; Liu, Manlu; Liu, Hongwei; Huo, Jianwen; Gou, Songlin; Su, Qing
Abstract: Compared with the traditional manipulator, the hyper‐redundant manipulator has the advantage of high flexibility, which is particularly suitable for all kinds of complex working environments. However, the complex space environment requires the hyper‐redundant manipulator to have stronger obstacle avoidance ability and adaptability. In order to solve the problems of a large amount of calculation and poor obstacle avoidance effects in the path planning of the hyper‐redundant manipulator, this paper introduces the 'backbone curve' approach, which transforms the problem of solving joint path points into the behaviour of determining the backbone curve. After the backbone curve approach is used to design the curve that meets the requirements of obstacle avoidance and the end pose, the least squares fitting and the improved space joint fitting are used to match the plane curve and the space curve respectively, and the angle value of each joint of the manipulator is limited by the algorithm. Furthermore, a fusion obstacle avoidance algorithm is proposed to obtain the joint path points of the hyper‐redundant manipulator. Compared with the classic Jacobian iteration method, this method can avoid obstacles better, has the advantages of simple calculation, high efficiency, and can fully reflect the geometric characteristics of the manipulator. Simulation experiments have proven the feasibility of the algorithm.